A STUDY ON DIGITAL LEARNING FOR MEDIA STUDENTS IN THE COVID-19 OUTBREAK - Chandan Saxena (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Digital learning is the process to provide knowledge, values and behavior with skill to anyone thorough new media. Digital Learning is a new media communications method which is done by multimedia devices like mobile phones, tablets, laptop etc. In this Digital learning process the most important tool for students are Google Classroom, Google hangout, podcast, zoom, Skype and so more similar applications. Around the world due to the COVID-19 outbreak every educational organization use these application to teach their students and give useful knowledge to them. To solve the queries and other study related problems teachers are using these application in India also. The methodology used in a study on digital learning for media students in the covid-19 outbreakis descriptive in nature and to analysis or understand the process of Digital learning for media students and about the problems and suggestion they faced during their Digital learning period. The results demonstrate that a study on digital learning for media students in the covid-19 outbreak increases the digital learning process among students and its attract students to take classes but they are facing many problems in that COVID-19 Outbreak.